On the status of Araripegryllus romualdoi (Insecta: Orthoptera: Grylloidea) from the Cretaceous Santana Formation of Brazil - Heads, Sam W. (Zootaxa, 2018)
The fossil cricket Araripegryllus romualdoi was described by Freitas et al. (2016) based on a single, very poorly preserved specimen from the Romualdo Member of the Lower Cretaceous Santana Formation; a deposit famed for the exceptional preservation of vertebrates in carbonate concretions (Martill, 1996, 2007). While abundant and diverse in the underlying Crato Formation (Martill et al., 2007 and contributions therein), fossil insects had not been reported from the Santana Formation prior to Freitas et al.’s paper. The occurrence of an insect in the Santana Formation is certainly noteworthy, but the description of a new species and its placement in the genus Araripegryllus are problematic, primarily because of the very poor preservation of the specimen. Here, problems associated with the diagnosis and placement of A. romualdoi are outlined, and the species declared a nomen dubium.